The Kanza: People of the South Wind - Crystal Douglas (Symphony in the Flint Hills, 2014)
The Kanza descended from a much older Mississippi Valley Siouan culture. Along with their close cultural relatives the Quapaw, Omaha, Ponca, and Osage, the Kanza are members of the Dhegiha (pronounced: they-GEE-hah) branch of Siouan peoples.
Keywords: Konza; Kansa; Native American; Indian; Osage; Omaha; Ponca; Dhegiha; people; peoples; Greenwood County; Great Plains; tradition; disease; invasion; territory; tribe; westward; Kaw Lake; Kaw; government; Kanza People; Washunga; Pawnee; Kaw Nation; homeland